Using UAV for Land Management during the COVID-19 Pandemic and its Post-Pandemic Potential - Olivatto, Tatiane Ferreira; Stanganini, Fábio Noel (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
After more than a year since the first case of COVID-19 in Brazil, some public sectors are still looking for tools to adapt their activities to epidemiological recommendations that require social distancing. Urban planning and territorial management are indispensable activities to the dynamics of cities and, therefore, cannot be interrupted. In this context, this article aims to investigate the use of Unmanned Aerial Vehicles (UAVs) as a territorial management tool, focusing on the Urban Technical Registration and Urban Land Regularization. From the case study methodology, it was verified in the experiences and current legislations that features related to property (such as constructions and vertical typology), urban infrastructure (e.g., manholes, sidewalks, lighting poles, hydrants, etc) and environmental aspects (mainly related to vegetation and water resources) need to be mapped for such purposes. We also considered the possibility of acquiring georeferenced and altimetric data. Finally, the use of orthophotos from UAVs has proved feasible for application in public territorial management in the context of epidemiological restrictions of isolation and social distancing imposed by the COVID-19 pandemic. This tool was also promising in the post-pandemic scenario, as it presents itself as a less invasive solution for property mapping.